Utilization Of Pop-Up Book as a Learning Media For Student Of Major Of Library Science - Nizamiyati, Nizamiyati; Sentiana, Fegi; Zahro, Faizafati Matus; Hilmiarhani, Faridah; Dinasta, Aldy Gyan; Fajriani, Nopi (UIN Raden Intan Lampung, 2022)
A library is a room, part of a building where books are stored for reading. Some people's understanding of libraries is also developing. There is no doubt that the library is a very important/vital tool for all levels of society, both for developed countries, developing countries and even poor countries. Therefore, it takes a graduate majoring in library science to process libraries. The Department of Library Science is a department that learns how to collect, analyze , process, manage, and communicate information from various media, such as documents, books, or digital. So the department of library science is required to prepare media to make it easier for prospective librarians to easily understand the processing of library materials in the library. One of the media that can help facilitate According to Dzuanda (2011: 11) Pop-Up Book is a book that has moving parts or has three-dimensional elements and provides a more interesting visualization of stories, starting from the image display. which can be moved ak when the page is opened. The purpose was made to help facilitate students in the learning process through the media pop-up book.